(untitled) (Hombre, Ciencia y Tecnología, 2018)
The objective of this research was to evaluate the biological diversity, frequency and abundance of the edaphic macrofauna associated with Pinus cubensis forests in Cupeyal del Norte Conservation Department, Alejandro de Humboldt National Park. The methodology of the Tropical Soil Biology and Fertility (TSBF) program was used to evaluate the fauna. The macrofauna of the soil was identified up to the level of order and family. There were identified 46 families distributed in 26 orders belonging to three subphylum (Crustacea, Cheliceriformes and Myriapoda) and to the phyla Annelida (earthworms) and Arthropoda (decapods, arachnids, insects and centipedes). The most frequent orders were Hymenoptera and Araneae; Mermicinae and Lycosidae among the families. In relation to abundance, the order Hymenoptera was evaluated as very abundant and the families Mermicinae, Lycosidae and Formicinae as abundant. When evaluating the stratum, the greatest wealth, frequency and abundance was found on the litter.